Factors influencing bike share among underserved populations: Evidence from three U.S. cities. (November 2022) - Dill, Jennifer; Ma, Jiahui; McNeil, Nathan; Broach, Joseph; MacArthur, John
Highlights: Recreation is a bigger motivator to use bikeshare than utility for people of color. Interactive sources of information may be effective at increasing use of bike share. Interactive sources of information may not be reaching POC. For all, having friends and family who bike share correlates with use and interest. Membership cost is a barrier for people who are interested and have tried bike share. Abstract: There is evidence that lower-income and people of color (POC) in the U.S. do not use bike share as much as higher-income and white people. Using data from residents living near stations in New York, Chicago, and Philadelphia, our analysis examines reasons for these disparities. While smaller shares of POC are members (vs higher-income white people), large shares of POC are interested in bike share. Among POC, having positive attitudes about bicycling and having family and friends that use bike share are strong predictors of interest in bike share. POC are also motivated to use bike share for recreational reasons. Receiving information from interactive sources may be effective at increasing bike share use and interest, though it is not clear whether these efforts have affected POC. Cost is a barrier for people who have tried bike share and are interested in using it in the future but are not members.